FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL TANGKAPAN NELAYAN DI KECAMATAN SUNGAI PINYUH KABUPATEN PONTIANAK - admin, feme (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT This research with the title Factor that Regard Fisherman Haul at Pinyuh's River district Pontianak's Regency, Intent to know capital influence, labour, distance sails through to go out to sea and fisherman experience to foot up fisherman haul at Pinyuh's River district Pontianak Regency West Kalimantan. Result observationaling to point out that capital variable (X1) having positive influence and signifikan to foot up haul (Y. ), with regression coefficient x 1 as big as 0,000608. Its mean each ascension totals capital (X1) 1 (one) grade therefore will experience ascension as big as 0,0608 grade of Y, on ceteris paribus. Labouring variable (X2) having for negative but not signifikan with regression coefficient 5.066. Distance variable sails through to go out to sea (X3 ) having for positive but not signifikan to haul with appreciative regression coefficient as big as 2.831. Experience variable (X4) pointing out relationship or negative influence(-0. 017) and don't signifikan, in opposition to theory and not rasional, but analyticaly writer can just factor experience just ascendant on quality and haul fish type and finally will ascendant also on price sells and fisherman income, In labouring purpose, Km 5 10 GT that most effective where each purpose satuan labouring result hauls as much 68,23 kg. If seen by its average for all fleet point out ratio as big as 34,37 kg per person per diem.